KARAKTERISASI DAN SKRINING FITOKIMIA EKSTRAK BUNGA TELANG (Clitoria ternatea L.) - Bebie Ayu Rismayuti; Risa Supriningrum; Supomo (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Characterization is a step to determine the quality of an extract of natural materials, which includes specific, non-specific parameters, and phytochemical screening. This study aims to determine the specific, non-specific characteristics and secondary metabolite compounds of telang flower extract. Telang flowers are made into powdered simplisia, and the drying shrinkage is determined. Furthermore, extraction was carried out using the maceration method with 70% ethanol solvent. The drying shrinkage of the simplisia was 10% and the extract yield was 43.8%. Specific characterization results include organoleptic observations in the form of thick blue-black extract with a distinctive odor and bitter taste. The average content of soluble compounds in water is 58% and the average content of soluble compounds in ethanol is 17.67%. Non-specific characterization results include an average moisture content of 21.93%. Average ash content of 5% and acid insoluble ash content of 2%. The average specific gravity was 1.015 g/ml and the results of mold/chamir numbers were 1 × 102 colonies/g and total plate numbers were 1.3 × 103 colonies/g. Secondary metabolite compounds contained in telang flower extract include alkaloids, flavonoids, saponins, steroids and terpenoids.